Improving the Flame Retardancy of Bamboo Slices by Coating With Melamine–Phytate via Layer-by-Layer Assembly - Lin, Peng; Xu, Yuchen; Hou, Junfeng; Zhang, Xiaochun; Ma, Lingfei; Che, Wenbo; Yu, Youming (Frontiers in Materials, 2021)
Bamboo is a rich natural resource in the Asia Pacific, and it is widely used in the construction and decoration industry. Meanwhile, bamboo is an extremely combustible natural polymer material. Herein, the bamboo slices were treated with melamine and phytic acid using layer-by-layer (LBL) assembly technology to improve their flame retardancy properties. The morphology and chemical composition of untreated and treated bamboo slices were measured by scanning electron microscopy equipped with energy dispersive X-ray analysis and Fourier transform infrared spectra. The results showed that two-dimensional melamine–phytate (MP) nanoflakes were successfully formed and deposited on the bamboo surface. The deposition of the MP coating caused the earlier degradation of the bamboo to form char, according to thermogravimetric analysis. The peak heat release rates of the treated bamboo slices were reduced by more than 28% compared to those of the untreated ones. The MP coating promoted the formation of thermally stable char, which was responsible for the significant improvement in flame retardancy. Besides, the char layer with excellent thermal resistance performed a vital role in suppressing flame spread.